2017
DOI: 10.1038/ncomms14601
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 sustains IL-7R-independent ILC2 and ILC3 development

Abstract: The signals that maintain tissue-resident innate lymphoid cells (ILC) in different microenvironments are incompletely understood. Here we show that IL-7 receptor (IL-7R) is not strictly required for the development of any ILC subset, as residual cells persist in the small intestinal lamina propria (siLP) of adult and neonatal Il7ra−/− mice. Il7ra−/− ILC2 primarily express an ST2− phenotype, but are not inflammatory ILC2. CCR6+ ILC3, which express higher Bcl-2 than other ILC3, are the most abundant subset in Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 51 publications
8
87
1
1
Order By: Relevance
“…Furthermore, ILC cross talk with activated T cells has been suggested by several studies 7,14,15 , arguing that disruption of T cell activation may impact upon ILC homeostasis. In addition, the cytokines that support ILC homeostasis, IL-7 and IL-15, are similarly required for T cell populations, and competition for these molecules has been proposed as a mechanism limiting ILC and T cell numbers 16,26 . Thus we considered that it would be informative to extend our analysis of ILC populations to mice deficient in both CD80 and CD86, where signals through CD28 are deficient and thus T cell activation is blocked ( Figure 5 A-C).…”
Section: Ilc Populations In Mice Lacking Activated T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ILC cross talk with activated T cells has been suggested by several studies 7,14,15 , arguing that disruption of T cell activation may impact upon ILC homeostasis. In addition, the cytokines that support ILC homeostasis, IL-7 and IL-15, are similarly required for T cell populations, and competition for these molecules has been proposed as a mechanism limiting ILC and T cell numbers 16,26 . Thus we considered that it would be informative to extend our analysis of ILC populations to mice deficient in both CD80 and CD86, where signals through CD28 are deficient and thus T cell activation is blocked ( Figure 5 A-C).…”
Section: Ilc Populations In Mice Lacking Activated T Cellsmentioning
confidence: 99%
“…Thus our aim was to extend this approach to compare ILC populations within a range of lymphoid and non-lymphoid tissues, reasoning that this would provide a useful resource from which to better develop understanding of ILC populations. Several studies have also indicated that ILC:T cell cross talk shapes the outcome of CD4 T cell responses 7,14,15 and that both cell types require common γ chain cytokines for their homeostasis [16][17][18] . Furthermore, ILCs express a number of costimulatory molecules whose expression is shared with T cells, although the role these molecules play in ILC function requires further investigation 3,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this phenotype relies on a compensatory mechanism involving TSLP signals through IL‐7Rα, in the absence of IL‐7. However, persistence of selective ILC2 and ILC3 populations has also been observed in Il7ra −/− mice and the presence of these residual cells is partially sustained by IL‐15 . These studies highlight the possibility that beyond the “canonical” ILC development, compensatory cytokine switches may occur in selective microenvironments.…”
Section: Jak/stat Pathway In Ilc Biologymentioning
confidence: 76%
“…D, Sorted total ILCs from controls or two STAT3 MT HIES patients were stimulated 20 min with media; IL-23 or IL-6 and pSTAT3 levels were measured by phospho-flow IL-7 is another cytokine critical for the generation, survival, proliferation, and maintenance of ILC3s in vitro and in vivo. [44][45][46][47][48][49] In this study, we…”
Section: Discussionmentioning
confidence: 99%